A Sustainable Solid Electrolyte Interphase for High‐Energy‐Density Lithium Metal Batteries Under Practical Conditions. Issue 8 (3rd January 2020) - Zhang, Xue‐Qiang; Li, Tao; Li, Bo‐Quan; Zhang, Rui; Shi, Peng; Yan, Chong; Huang, Jia‐Qi; Zhang, Qiang
Abstract: High‐energy‐density Li metal batteries suffer from a short lifespan under practical conditions, such as limited lithium, high loading cathode, and lean electrolytes, owing to the absence of appropriate solid electrolyte interphase (SEI). Herein, a sustainable SEI was designed rationally by combining fluorinated co‐solvents with sustained‐release additives for practical challenges. The intrinsic uniformity of SEI and the constant supplements of building blocks of SEI jointly afford to sustainable SEI. Specific spatial distributions and abundant heterogeneous grain boundaries of LiF, LiN x O y, and Li2 O effectively regulate uniformity of Li deposition. In a Li metal battery with an ultrathin Li anode (33 μm), a high‐loading LiNi0.5 Co0.2 Mn0.3 O2 cathode (4.4 mAh cm −2 ), and lean electrolytes (6.1 g Ah −1 ), 83 % of initial capacity retains after 150 cycles. A pouch cell (3.5 Ah) demonstrated a specific energy of 340 Wh kg −1 for 60 cycles with lean electrolytes (2.3 g Ah −1 ). Abstract : A solid electrolyte interphase (SEI) was proposed for practical high‐energy‐density Li batteries. The intrinsic uniformity and the constant supplements of building blocks of SEI jointly afford a sustainable SEI. A pouch cell with a specific energy of 340 Wh kg −1 underwent 60 cycles with a retention of 90 %.